Cloning and transformation of rice gene Os992 and its sensitivity to glucose - BAI Yang; LIU Dong-feng; HAO Zhong-na; WANG Zheng-yi; GUO Ze-jian (浙江大学学报. 农业与生命科学版)
A rice (Oryza sativa) transcription factor Os922 gene of AP2/EREBP species was cloned by PCR from rice cDNA library, and constructed CoU-Os922 overexpression vector. The vector was transformed into rice Xiushui11 calli by Agrobacterium-mediated method under light co-culture conditions, and obtained transgenic plants. Analyzing hygromycin-resistant plants by PCR and Southern blot method confirmed that Os922 was integrated into rice genome. The expression of Os922 in T1 transgenic plants showed the root development was restrained by glucose, and this sensitivity to glucose suggested that Os922 may be relative to the sugar signal transduction.